The formation and symbiotic activity of nodule bacteria of pea plants mustache in the Forest-Steppe of Ukraine - Пилипенко, В. С. (Scientific Progress & Innovations, 2016)
The basic results of research conducted in the northern part of Right-Bank of Forest-Steppe zone of Ukraine for 2014–2016 years on typical black earth are presented. We established that the varietal characteristics of culture, preplant treatment of seeds and fertilizer had a positive impact on the formation of the quantity and mass of nodules in pea plants. The most favorable conditions for the formation of symbiotic system are created by the combination of sowing seed inoculation with fertilizer in version K1 + +N10P10 BBCH13-19 + N10P10 BBCH55-59 + N10P10 BBCH61-65. Against the background of mineral fertilizers N30P90K90 the formation and performance of the device symbiotic pea plants amplified. The indicated level of mineral nutrition is effective and for the sowing seeds that are not subject to inoculation. The high level of mineral nitrogen negatively affects on the symbiotic relation between pea plants and nodule bacteria.